(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2018)
The composition and landings of sharks were determined based on the collected data in 2012 from the monitoring of artisanal fishing fleet directed to the fishery of big pelagic fishes carried out by the staff of Instituto Nacional de Pesca. The sharks landing was estimated in 9361.0 tonnes which representes an increase of 2.7% compared to 2011 but a decrease of 15.5% compared to 2010. Alopias pelagicus and Prionace glauca were species commonly landed and Manta was the most representative fishing port in terms of volumes landed. These shark species were captured as bycatch from the artisanal fleet that captures tunas, weevil and sword using coarse longline. Regarding the sexual maturity of shark species, a high quantitaty of immature individuals were registered in the landings of C. falciformis, S. zygaena and I. oxyrinchus, while A. pelagicus and P. glauca had a different behavior when registering more than 50% of mature organisms. The sharks catch areas were located mainly southwest of the Galapagos Islands in the case of the fleet of vessels that catch tuna, weevil and swordfish and in international waters between 00°02’ N and 12°00’ S for dorado.